1996
DOI: 10.1046/j.1365-2141.1996.423958.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominant expression of the long isoform of Bcl‐x (Bcl‐xL) in human lymphomas

Abstract: Bcl-x is a member of the bcl-2 family of proteins which are characterized by their ability to modulate apoptosis. Alternative splicing results in two distinct bcl-x mRNAs encoding a long isoform, bcl-xL, which acts as a bcl-2 agonist; and a short isoform, bcl-xS, which inhibits bcl-2 effects. The aim of the study was to determine whether bcl-x is expressed in lymphoma tissues and to characterize the respective production of bcl-xs and bcl-xL. We investigated the expression of bcl-x mRNA in a series of 50 non-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 15 publications
(38 reference statements)
3
58
1
1
Order By: Relevance
“…We analysed Bcl-2 expression using reverse transcriptase-polymerase chain reaction (RT-PCR) in the 18 NHL cases, and found no correlation between the level of expression and the sensitivity to Fas killing (data not shown). These results do not exclude a possible role of other members of the Bcl-2 family, such as Bcl-xL, which was demonstrated to decrease Fas killing when transfected into apoptosis-sensitive myeloma cells (Gauthier et al, 1996); we reported previously that the majority of human NHLs express substantial amounts of Bcl-xL (Xerri et al, 1996). The defect could be linked alternatively to the effectors of apoptosis including caspases, which are known to control the distal point of a common apoptotic pathway shared by many cell death inductors (Casciola-Rosen et al, 1996;Henkart, 1996).…”
Section: Discussioncontrasting
confidence: 58%
“…We analysed Bcl-2 expression using reverse transcriptase-polymerase chain reaction (RT-PCR) in the 18 NHL cases, and found no correlation between the level of expression and the sensitivity to Fas killing (data not shown). These results do not exclude a possible role of other members of the Bcl-2 family, such as Bcl-xL, which was demonstrated to decrease Fas killing when transfected into apoptosis-sensitive myeloma cells (Gauthier et al, 1996); we reported previously that the majority of human NHLs express substantial amounts of Bcl-xL (Xerri et al, 1996). The defect could be linked alternatively to the effectors of apoptosis including caspases, which are known to control the distal point of a common apoptotic pathway shared by many cell death inductors (Casciola-Rosen et al, 1996;Henkart, 1996).…”
Section: Discussioncontrasting
confidence: 58%
“…High Bcl-x(L)/Bcl-x(s) ratios are observed in a variety of cancer types, consistent with an important role for the long isoform in cancer cell survival (Xerri et al 1996;Olopade et al 1997;Takehara et al 2001). This likely reflects a reduction in Bcl-x(s) in cancer, as an examination of endometrial carcinomas showed a down-regulation of Bcl-x(s) mRNA compared with normal endometrial tissue, with the extent of Bcl-x(s) down-regulation correlated with clinical staging .…”
Section: Bcl-xmentioning
confidence: 59%
“…The present report suggests a specific antiapoptotic role of Bcl-xL in the apoptotic resistance of lymphoma cells, as we observed a lower level of Bcl-xL in normal B-cells, in accordance with our previous report. 37 Increased Bcl-xL levels were also reported in FL cells which survive upon CD40 stimulation. 38 Bax expression levels may be also an important parameter, as we found a significant difference between NHL cells and normal B cells.…”
Section: Discussionmentioning
confidence: 96%